Betroot (Beta vulgaris) administration to anemic pregnant women for increasing hemoglobin level - Rr Catur Leny Wulandari; Is Susiloningtyas (Universitas Airlangga, 2020)
Objective: To identify the effectiveness of beet juice administration on hemoglobin level of anemic pregnant women. Materials and Methods: This was an experimental quantitative study using pretest-posttest design with a total sample of 30 patients who were divided into 2 groups of treatment groups (beetroot + Fe) and control group (Fe). The treatment was carried out for 14 days. Before and after the treatment, the samples were subjected to hemoglobin examination. Data in this study were the difference between pre-test and post-test values, the results of normality test with Shapiro Wilk, and, to identify the difference between pre-test and post-test, the results of Wilcoxon Test for abnormal data and Paired T-Test for normal data. Results: Mann Whitney Test results between treatment and control groups revealed p (0.023) < alpha (0.05). There was a significant difference in hemoglobin levels between TM III pregnant women with anemia receiving beets and those receiving Fe tablets only. Conclusion: Minimum Hb increase before and after the administration of Fe and beetroot juice to pregnant women was 17.7 gr% and the maximum Hb level was 0.8 gr%.